Outcome and requirement for surgical repair following prenatal diagnosis of ventricular septal defect. (July 2014) - Mosimann, B.; Zidere, V.; Simpson, J. M.; Allan, L. D.
ABSTRACT Objective To document outcome following prenatal diagnosis of ventricular septal defects (VSDs), particularly associated anomalies and the requirement for surgical closure of the defect. Methods All cases of prenatal diagnosis of a VSD made by fetal cardiologists at a tertiary fetal medicine referral center in the period January 2002 to December 2011 were extracted from our database. Data regarding fetal cardiac diagnosis, extracardiac anomalies, nuchal translucency thickness and karyotype were noted. Results A total of 171 cases fulfilled our selection criteria. Of these, 69% were diagnosed with a perimembranous VSD and 31% with a muscular defect. The median gestational age at diagnosis was 21 + 6 (range, 12 + 0 to 37 + 3) weeks. Owing to severe extracardiac or genetic conditions, pregnancy resulted in intrauterine death or termination in 49% cases, and postnatal death occurred in 9% of cases. Seventy‐two babies were liveborn, and were regarded as potential surgical candidates if hemodynamics suggested that surgery was indicated. Surgical closure of the VSD proved necessary in 50% of the patients with a perimembranous VSD and 13% of those with a muscular VSD. All patients operated on survived surgical repair. No karyotypic abnormalities were identified in fetuses with VSDs that had normal first‐trimester screening and no other sonographic abnormalities. Conclusions A high proportion of VSDs diagnosed during fetal life (29%) require postnatal surgical intervention. The assessment of hemodynamic significance from fetal echocardiography is imperfect. The presence of extracardiac abnormalities or abnormal results on first‐trimester screening has a major impact on the incidence of karyotypic abnormalities in affected fetuses. This should inform discussions with parents about invasive testing. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.